Interventions strategy reducing postpartum fatigue: a literature review - Tuan Van Nguyen; Wantonoro Wantonoro; Phuong Viet Nguyen; Liem Thanh Nguyen (Universitas 'Aisyiyah Yogyakarta, 2022)
Background: Postpartum fatigue is a severe concern for mothers worldwide, and fatigue has a high prevalence rate. Fatigue symptoms impact postpartum maternal role attainment and are also considered to affect her quality of life adversely. Objective: This study aimed to identify interventions strategy reducing postpartum fatigue. Methods: Literature reviews were conducted with PubMed, Scopus, Cochrane Library, Web of Science, and Google Scholar database. Inclusion criteria (1) randomized controlled trials or quasi-experimental studies (2) strategies on mothers with postpartum fatigue study (3) English. Full text. Two reviewers will independently perform selection articles, quality assessment, and data extraction. The methodology's quality and evidence level will be graded using the modified Jadad Scale. Results: Eight studies were included (819 postpartum women and, executed nine kinds of interventions). Aerobic gymnastic exercise used DVD significantly decreased levels of postpartum fatigue and also significantly improved stress and postpartum sleep quality. The professionally-led telephone support significantly decreased fatigue and depression, anxiety, stress, and significantly higher self-care behavior. In addition, most instruments used to measure postpartum fatigue are Postpartum Fatigue Scale (PFS) and Fatigue Severity Scale (FSC). Conclusions: Aerobic gymnastic exercise used DVD and professionally-led telephone support are recommended as strategic interventions for reducing postpartum fatigue.